Exploring Incongruence in Mentoring Dyads in Indian Firms: The Protégé Perspective. (December 2018) - Kumar, Payal
Abstract: This study seeks to explore whether the negative mentoring experiences (NMEs) of protégés in Western samples are generalizable, or whether there are possibly NMEs unique to the Indian cultural context. The finding of this exploratory study suggests that the most frequently occurring NME for protégés was mismatch in the membership of social group, as per regional, caste or religious orientation. While Western mentoring models are being practised widely in corporate workplaces in India, the process of enculturation and feeling of belonging to an India-specific social group is strong enough to negatively impact mentoring relationships such that these protégés perceive themselves to be "out-group" members. Managers may consider pairing mentors and protégés taking into consideration demographic profiling.